Abstract Labour: A Critique - Cohen, Jim. author. aut Link
XXXI, 156 p.
Keywords: These five philosophical essays are designed to constitute a unified whole, in both their critical and their constructive dimensions. Vincent addresses the crisis of meaning, the repetitiousness of technological processes and mechanisms and the declining sense of the real in political life.